Clinical outcomes and trans-syndesmotic screw frequency after posterior malleolar fracture osteosynthesis. Issue 3 (March 2021) - Marques Ribeiro, H.; Silva, J.; Teixeira, R.; Fernandes, P.; Sobral, L.; Rosa, I.
Highlights: Posterior malleolus fragment (<25% of articular surface) osteosynthesis significantly increase the clinical and functional outcomes. Posterior malleolus fragment (<25% of articular surface) osteosynthesis significantly decreases the need of additional trans-syndesmotic osteosynthesis. Abstract: Aim: This study aimed to evaluate the clinical outcomes and the trans-syndesmotic screw frequency after trimalleolar ankle fractures with a posterior malleolus fracture involving <25% of the articular surface. Material and Methods: Retrospective comparative study. Patients with trimalleolar ankle fracture who underwent surgery between January 2011 and January 2018 were identified within the departments' fracture database. General demographics, treatment details, and fracture specific details (CT-scans) were assessed. Patients were grouped per the posterior malleolus fragment treatment: osteosynthesis (group 1) and non-osteosynthesis (group 2). Results: 64 patients, 58.6 ± 17.8 years (range: 23–75), 68.8% female were eligible and follow up time was 43.1 ± 22.2 (range 24–96) months. The mean size of the posterior malleolus fragment was 14.7 ± 5.3% (range: 5–24). Posterior malleolus fragment treatment distribution: osteosynthesis (group 1) 31.2% and non- osteosynthesis (group 2) 68.8%. Group 1 showed significantly better clinical outcomes ( p <0.05), AOOS (93.9 ± 5.79 (range: 73–99), AOFAS (91.5 ± 6.22 (range: 72–100) and VAS (0.8 ± 1.22 (range: 0–5) compared to Group 2, AOOS (84.25±8.34 (range: 63–100); AOFAS (84.75±8.05 (range: 58–100) and VAS (1.7 ± 1.38 (range: 0–6). Osteosynthesis of the posterior malleolus fragment significantly reduced the frequency of trans-syndesmotic screw (0%) compared to non-osteosynthesis posterior malleolus fragment (15.9%) ( p < 0.05). The EQ-5D score was better in group 1 (1.08±0.27 (range: 1–2.2) compared to group 2 (1.27 ± 0.27 (range: 1–2.4) but with no statistical significance ( p > 0.15). Conclusion: Posterior malleolus fragments (<25% of the articular surface) have significantly better clinical outcomes and significant decrease in trans-syndesmotic screw need following osteosynthesis.